The Hulong hybrid grouper (Epinephelus fuscoguttatus♀×Epinephelus lanceolatus♂) has invaded the coastal waters of Hainan Island, China - Zhang, Xiang; Li, Jianlong; Chen, Sizhu; Yang, Qingyan; Ji, Fei; Luo, Huigui; Ding, Shaoxiong (Frontiers in Marine Science, 2024)
Hybrid groupers, including the Hulong hybrid grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂), have become increasingly popular in mariculture across the southwest Pacific, raising concerns about their potential to cause biological invasions. First developed in Malaysia in 2007 and introduced to mainland China in 2009, the Hulong hybrid grouper has been sighted in the coastal waters of Hainan Island, China, for over a decade. This study examines the species' distribution, survival, and ecological impacts in these waters. From 2019 to 2023, social surveys, specimen collections, and field observations confirmed the widespread presence of the Hulong hybrid grouper, particularly in inshore reefs and artificial structures. Age determination and gonadal analysis demonstrated their long-term survival and reproductive maturity in the wild. The introduction of this species resulted from both unintentional escapes from aquaculture facilities and intentional releases. This research represents the first documented case of an artificial hybrid marine fish invading and establishing a population in the wild, with potential negative ecological impacts such as interspecies competition, disease transmission, and genetic pollution.